C3 glomerulopathy - Pickering, Matthew (Henry Stewart Talks, 2017)
Defining C3 glomerulopathy (C3G), Pathogenesis of C3G, The strong association with abnormalities in complement regulation in C3G, Complement as the major driver of inflammation and kidney injury in C3G, Lessons from animal models in C3G, Therapeutic considerations for C3G